Fort Oranje tourism: Community and cultural reproduction in the city of Ternate - Dhifan Nurfadhlih; Rimbo Gunawan (Universitas Ahmad Dahlan, 2026)
The increasing utilization of cultural heritage sites as tourism spaces raises important questions regarding how communities contribute to the preservation and transformation of cultural meaning. However, most studies on cultural reproduction have primarily focused on formal institutions such as education and family, leaving the role of public heritage spaces underexplored. This study aims to examine the process of cultural reproduction within community activities at Fort Oranje, Ternate City, and to analyze how the site functions as a social arena in the perspective of Pierre Bourdieu. The research contributes to the development of cultural reproduction theory by demonstrating the significance of community-driven practices in shaping the meaning and sustainability of cultural heritage tourism. This research employs a qualitative method with a case study approach. Data were collected through non-participant observation, in-depth interviews with site managers, community members, conservationists, and tourists, as well as documentation. The findings reveal that Fort Oranje, as a cultural heritage site, has been reinterpreted as a dynamic social and cultural space by communities such as the Ternate City Community Network (JARKOT) and Ternate Creative Space. Cultural reproduction occurs through the interaction of field (Fort Oranje), agents (communities), and practices (cultural activities), supported by various forms of capital, including social, cultural, economic, and symbolic capital. This study concludes that cultural reproduction is not limited to formal institutions but can also emerge through repeated cultural practices in public heritage spaces.